PENGARUH METODE PEMBELAJARAN GQGA TERHADAP HASIL BELAJAR MATEMATIKA MATERI PEMBAGIAN UNTUK SISWA KELAS II SDN NGADI - Dewitasari, Mulia; Zaman, Wahid Ibnu; Mukmin, Bagus Amirul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to determine the effect of the Giving Question and Getting Answer (GQGA) learning method on the Mathematics learning outcomes of class II students at SD Negeri Ngadi. The study was conducted through the experimental method of pretest-posttest Control Group design. The subjects of this study were 30 students, with class IIA as the experimental class totaling 15 students and class IIB as the control class also totaling 15 students. The data collection tool used was a learning outcome test on division material. The data analysis technique used statistical analysis pair sample T-test. The results of the study showed a significant value of 0.00 <0.05. So H0 is rejected and Ha is accepted, it can be concluded that there is an effect of learning outcomes in the experimental group on the ability to achieve Mathematics learning outcomes on division material among class II students who use the GQGA learning method.